11+8x-11-6x+6=11+(8x-11)-6x+6

Simple and best practice solution for 11+8x-11-6x+6=11+(8x-11)-6x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+8x-11-6x+6=11+(8x-11)-6x+6 equation:


Simplifying
11 + 8x + -11 + -6x + 6 = 11 + (8x + -11) + -6x + 6

Reorder the terms:
11 + -11 + 6 + 8x + -6x = 11 + (8x + -11) + -6x + 6

Combine like terms: 11 + -11 = 0
0 + 6 + 8x + -6x = 11 + (8x + -11) + -6x + 6
6 + 8x + -6x = 11 + (8x + -11) + -6x + 6

Combine like terms: 8x + -6x = 2x
6 + 2x = 11 + (8x + -11) + -6x + 6

Reorder the terms:
6 + 2x = 11 + (-11 + 8x) + -6x + 6

Remove parenthesis around (-11 + 8x)
6 + 2x = 11 + -11 + 8x + -6x + 6

Reorder the terms:
6 + 2x = 11 + -11 + 6 + 8x + -6x

Combine like terms: 11 + -11 = 0
6 + 2x = 0 + 6 + 8x + -6x
6 + 2x = 6 + 8x + -6x

Combine like terms: 8x + -6x = 2x
6 + 2x = 6 + 2x

Add '-6' to each side of the equation.
6 + -6 + 2x = 6 + -6 + 2x

Combine like terms: 6 + -6 = 0
0 + 2x = 6 + -6 + 2x
2x = 6 + -6 + 2x

Combine like terms: 6 + -6 = 0
2x = 0 + 2x
2x = 2x

Add '-2x' to each side of the equation.
2x + -2x = 2x + -2x

Combine like terms: 2x + -2x = 0
0 = 2x + -2x

Combine like terms: 2x + -2x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4(n-5)+15n=-4(-10n+3)-21n-8 | | 16=0 | | (x-3)x(x-5)= | | 5(3x-6)=9x-12 | | y-3=-3(x+3) | | y-3=-3(x-1) | | y+3=-3(x-3) | | k-16=-36 | | 4y+2=x | | -7t/2=7 | | y+3=-3(x+1) | | 3+2x-9=5x-21 | | 4xsquared+100=0 | | -3(5x+3)-2(x-6)= | | 1/2x2-3 | | c-79.9=-104.9 | | 3-3x=7x+12 | | w+6=57 | | 24v^4w^9-18vw^3y^5= | | 5x?5x= | | 693950=.798750X | | 693950=.798750 | | 8xy-9x= | | 400x+36000=2000x+12000 | | y=5/6(126) | | 5/6-1/3n=5p-2np | | 1-2x=6-4x | | 4X-2.5=7.4 | | 7b-16=-45 | | .08X=700 | | 7-(3n-8)=-6 | | 7x^2+3=5 |

Equations solver categories